Performance evaluation of finite difference and finite element methods applied to flexible thin plate for active vibration control - Tavakolpour, Ali Reza (World Scientific And Engineering Acad And Soc, 2008)
This research presents an investigation into the performance evaluation of Finite Difference (FD) method in modeling a flexible rectangular thin plate structure for real-time application. Using FD method, an appropriate model of a thin plate was derived and the corresponding natural frequencies were estimated. Then, Finite Element (FE) modeling of the plate system was implemented using the ANSYS software and the corresponding modes of vibration were computed by modal analysis. The obtained vibration modes for both models were then evaluated and compared. The effectiveness of FD method for real time application were verified by comparative assessment of the obtained natural frequencies with the exact value reported by other researchers. The FD method was found to be the better choice than FE method to model a plate structure for real-time active vibration control.